Influence of the phosphoorganic insecticide Phenitrothion on the structure of the syrphid coenosis (Syrphidae, Diptera) in a root zone of a beet ecosystem - Markova, Emilia (Macedonian Journal of Ecology and Environment, 1996)
The effect of the phosphoorganic insecticide phenitrothion on a basic population and coenotronic parameters of the structure of the syrphid community was studied in a field experiment.